الشِّاهد الشِّعري في كتابِ شذا العَرفِ في فنِّ الصَّرفِ لِلحَملاوي صُورُهُ وسياقاتُهُ - Abo Haneefa Omer Alshareef Ali Omer (Al-Zahra: Journal for Islamic and Arabic Studies)
This research investigates the poetic witness in the book Shaza Al-Orf in the Art of Morphology, which is a topic that needs to be studied and collected to know (Al-Hamalawy) employment of poetic evidence and prove the morphological issues with them. know Sheikh (Al-Hamalawy) is considered one of the prominent scholars of linguistics in the modern era and his authentic reference under investigation got widespread fame for language learners. In it, its author followed the approach of the ancients, so the poetic evidence came in it, either to indicate the regularity of a morphological rule or its abnormality from the ordinary, or to clarify the structure of a word, or to prove a morphological rule, just as in most of his poetic evidence - which amounted to eighty-seven witnesses - he was satisfied with mentioning (and saying), Or (and the saying of the poet) without attributing it to its owners, as the case  of ancient authors. In the contexts of the poetic witness and the forms of his appearance in the book, he varied, and the images presented by his author differed, as he is either in one verse of al-Qaeda the subject of martyrdom, or in two verses, or in a half of a verse that has a completeness that is not mentioned, or a bifurcated witness that varied between one to three.